Hepatitis C virus (HCV) genotype 1 NS5A resistance-associated variants are associated with advanced liver fibrosis independently of HCV-transmission clusters. (April 2019) - Parczewski, M.; Kordek, J.; Janczewska, E.; Pisula, A.; Łojewski, W.; Socha, Ł.; Wawrzynowicz-Syczewska, M.; Bociąga-Jasik, M.; Szymczak, A.; Cielniak, I.; Siwak, E.; Mularska, E.; et al.
Abstract: Objectives: The aim of the study was to characterize the differences in the frequencies of NS3 and NS5A resistance-associated variants (RAVs) among Polish therapy-naive genotype 1 (G1) hepatitis C virus (HCV)-monoinfected and human immunodeficiency virus (HIV)/HCV-coinfected patients including clustering patterns and association of RAV frequency with liver fibrosis. Methods: NS3/NS5A RAVs were identified by population sequencing in 387 directly acting antiviral treatment-naive G1-infected individuals (54 with genotype 1a (G1a) and 333 with genotype 1b (G1b)). Liver fibrosis was assessed based on histopathology or ultrasound elastography. Phylogenetic clusters were identified using maximum likelihood models. For statistics, chi-squared or two-sided Fisher's exact tests and multivariate logistic regression models were used, as appropriate. Results: NS3 RAVs were found in 33.33% (18/54) for G1a and 2.62% (8/297) for G1b whereas NS5A variants were present in 5.55% (3/54) G1a and 9.31% (31/333) G1b sequences. Variations in NS5A 31 and 93 codon positions were found only in G1b (4.2% (14/333) for L31I/F/M and 5.39% (17/333) for Y93H). NS5A RAVs were more frequent among patients with advanced liver fibrosis (17.17% (17/99) for F3–F4 versus 6.94% (17/245) for F0–F2; p 0.004) or liver cirrhosis (20.34% (12/59) for F4 versus 7.72% (22/285) for F0–F3; p 0.003). Liver cirrhosis (F4) was associated with higher odds ratio of the NS5A RAVs among HCV-infected patients (odds ratio 2.34, 95% CI 1.004–5.291; p 0.049). NS5A RAVs were less frequent among sequences forming clusters and pairs (5.16% (8/155) versus 11.21% (26/232); p 0.039). Conclusions: Presence of NS5A RAVs correlated with progression of liver fibrosis and represents de novo selection of variants rather than transmission of drug resistance. Hence, the presence of NS5A RAVs may be a predictor for a long-lasting HCV infection.